Hubungan Pengetahuan Ibu Nifas Tentang Pemberian Asi Secara Rutin Dengan Bendungan Asi Di Wilayah Kerja Puskesmas Singgani Kota Palu - Kristiani, Yuni; Mirda (Akademi Kebidanan Palu Sulawesi Tengah, 2019)
Damage to breast milk is freezing in the breast due to increased venous and lymph flow causing painaccompanied by an increase in body temperature. Factors that cause ASI dams are emptying of mums that arenot as complete as the sucking factor of babies who are not active because of the frequency of breastfeedingbabies that are not routine, improper breastfeeding factors, croton milk set, milk nipples too long. The aim of thestudy was to determine the relationship between knowledge of postpartum mothers about routine breastfeedingwith ASI Dam in the Working Area of Singgani Public Health Center, City of Palu This study is a type ofanalytical research with a cross sectional approach. The population in this study were all normal postpartummothers, whose breast milk did not come out on days 1-3, Primigarvida and Multigravida mothers in theWorking Area of Singgani Health Center, City of Palu. The sample of this study was 33 respondents. Thesampling technique was accidental sampling. The analysis used in this study is univariate and bivariate analysis.The results of the study showed that 33 respondents had good knowledge of 26 respondents 78.8%, motherswho had poor knowledge were 7 respondents 21.2%, mothers who had ASI dams were 26 respondents 78.8%and mothers who did not ASI dam occurred at 21.2% of 26 respondents with good knowledge as many as 20respondents who had ASI dams and 6 respondents who did not have ASI dams from 7 mothers who were notwell informed as many as 6 ASI dams and 1 respondent did not have ASI dams. The Fisher Exact Test testresults show that the p value is 0.531> 0.05. Conclusions there is no relationship between routine breastfeedingand ASI dams.